2021
DOI: 10.1192/j.eurpsy.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation of depression and adverse outcomes in patients undergoing vascular surgical interventions: A retrospective cohort study using a large mental health database in South London

Abstract: Background Patients with depression are more susceptible to cardiovascular illness including vascular surgeries. However, health outcomes after vascular surgery among patients with depression is unknown. This study aimed to investigate associations of depression with post-operative health outcomes for vascular surgical patients. Methods A retrospective observational study was conducted using data from a large mental healthcare provider and linked national hospitalization data for the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Previous studies, including our own work, have suggested that postoperative surgical outcomes are commonly worse in patients with mental health problems [ 10 , 11 ]. They may therefore constitute a potentially high-risk group for adverse outcomes after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including our own work, have suggested that postoperative surgical outcomes are commonly worse in patients with mental health problems [ 10 , 11 ]. They may therefore constitute a potentially high-risk group for adverse outcomes after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Readmissions were found to be generally increased in patients with MHD. 4,9,14,17,20,23,30,33-35 Notably, patients with MHD undergoing general surgery procedures had a 14.5% chance of readmission compared to 3.7% for those without MHD (P = .009). 9 Similarly, Litz, et al, conducted a retrospective analysis on 30-day readmission rates of bariatric surgery patients who had MHD and found a 34% greater odds of readmission on average in those with MHD compared to those without MHD (OR 1.34, 95% CI 1.19-1.51).…”
Section: Resultsmentioning
confidence: 98%
“…Some studies found MHD negatively impacted mortality. 17,33,36-38 Notably, Abrams, et al’s, study focused on surgical mortality and found those with an MHD had a higher 30-day mortality (OR 1.21, 95% CI 1.07-1.37, P = .003). However, their analysis also included cardiothoracic procedures and extracranial neurosurgical procedures in addition to general surgery procedures.…”
Section: Resultsmentioning
confidence: 98%
“…12,32–34 Depression has been recognized as a prevalent comorbidity among patients with PAD and has recently been associated with higher rates of MACE and MALE outcomes, as well as outcomes such as length of stay and readmission after revascularization. 35–40 Simple tools such as the Geriatric Depression Score (GDS) or the Patient Heath Questionnaire (PHQ)-9 can be used to assess for depression. 41,42…”
Section: Special Considerations In Pad: Risk Amplifiers Health Dispar...mentioning
confidence: 99%